INVENTARISASI DATA POTENSI SUMBERDAYA WILAYAH PESISIR KABUPATEN SUMENEP - Firman Farid Muhsoni; Muhammad Syarief; Mahfud Effendi (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2011)
Aim of this research is to inventory data of the coastal area resource potential in Sumenep residence (the use of land in coastal area, mangrove, coral reef). The variables collected comprise of physical variables and land ecology, topography (biometrics), coastal area ecosystem (the land utility, coral reef and mangrove), type of soil. The map of land utility obtained from the interpretation of satellite image (citra satelit) by Maximum Likelihood method to get surface area (6.632 ha), field (4.032 ha), dry field (131.223 ha), fishpond (4.143 ha), forest (21.761 ha), mangrove (11.742 ha), coral reef obtained by Lizenga Method (47.760 ha). The depth average of Sumenep waters 51.9 m. The height average of land 95.27 m. The length of river is 1,736 km. The dominant kind of land is Kompleks Mediteran Merah and Litosol. The road length is 4.160.5 km. Keywords : Anguilla bicolor, artificial feed, Tubifex tubifex, protein retention, fat retention, energy retention.